2020
DOI: 10.1021/acs.jafc.9b08215
|View full text |Cite
|
Sign up to set email alerts
|

Tomato Chlorosis Virus Minor Coat Protein as a Novel Target To Screen Antiviral Drugs

Abstract: Minor coat protein (mCP), an important component of tomato chlorosis virus (ToCV), plays a significant role in the process of virus assembly and movement and is directly related to the virus−insect transmission. Therefore, ToCV mCP could be considered as a potent target for anti-ToCV drugs. In this study, ToCV mCP was first cloned, expressed, purified, and a novel target to screen the antiviral agents. The results showed that some antiviral compounds bound to ToCV mCP with strongly affinities in vitro, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…It is a chiral triazole fungicide employed to control plant pathogens. The fungicidal mechanism of such pesticides inhibits ergosterol biosynthesis and cell wall synthesis ( Song et al, 2019 ; Yang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is a chiral triazole fungicide employed to control plant pathogens. The fungicidal mechanism of such pesticides inhibits ergosterol biosynthesis and cell wall synthesis ( Song et al, 2019 ; Yang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in our follow-up studies, we gradually found that dithioacetal derivatives showed good biological activities against a variety of plant viruses, such as the common plant viruses TMV, 24 potato virus Y, 25 CMV, 26 and ToCV. 27,28 At the same time, we found that pyrimidine derivatives present good fungicidal, 29 insecticidal, 30 herbicidal, 31 and bactericidal 32 activities. However, the biological activities of 4(3H)-quinazolinone derivatives, dithioacetal derivatives, or pyrimidine derivatives against TSWV have not been reported.…”
Section: ■ Introductionmentioning
confidence: 75%
“…Then, on the basis of q 2 and ONC, the CoMFA and CoMSIA models were obtained through noncross validation, and the Fisher-statistic values ( F ), noncross-validation coefficient ( r 2 ), and standard error of the estimate (SEE) were obtained. According to the existing method, the external predictive correlation coefficient ( Q 2 F1 , Q 2 F2 ) and concordance correlation coefficient (CCC) of the models were calculated. , …”
Section: Methodsmentioning
confidence: 99%
“…For example, harpin binding protein-1 is a potential target activated antiviral response in tobacco by antiviral agent dufulin [ 81 ], and tomato chlorosis virus (ToCV), CP play significant roles in sustaining the methyl cycle and S-adenosylmethionine-dependent methyltransferase activity and its minor CP play important roles in silencing suppression activity to counteract the RNA silencing-mediated defense response of the host [ 82 , 83 ]. Glucopyranoside derivatives, pyrimidine derivatives, 4(3H)-quinazolinone derivatives, and novel quinazolinone sulfide inhibitors targets ToCV coat protein with high anti-ToCV activity [ 84 , 85 , 86 , 87 ], and its minor coat protein is regarded as a novel target for the new green anti-ToCV inhibitors [ 88 ].…”
Section: Discussionmentioning
confidence: 99%